The Effectiveness Of Flogging Punishment On Public Legal Awareness In Aceh Province: A Sociology Of Jurisprudence Perspective - Siti Syafa Az Zanubiya; Nefrisa Adlina Maaruf; Atik Winanti (JURNAL HUKUM SEHASEN, 2023)
Basically, it is not easy to make efforts to improve legal awareness in society without encouragement from individual communities. So that there needs to be more serious participation in socialization so that people can understand clearly and implement legal awareness properly. Flogging punishment is expected to be able to fulfill philosophical, juridical and sociological tendencies towards public legal awareness. This research is empirical legal research that uses primary data sources, namely that the author identifies and conceptualizes law as a real and functional social institution, which tends to be quantitative, based on primary data. The data obtained comes from quantitative observations that discuss the effectiveness of law as a means of social control, as well as the bond between law and social changes. The results of this study indicate that the implementation of flogging punishment in increasing public legal awareness is still considered not optimal. This is due to several reflections of the life of the people of Aceh today has cultivated indifference. Sociology of Law or better known as Sociology Jurisprudence has the task of revealing the causes of the discrepancy between the orderly society that is aspired to with the orderly society in reality.